2003
DOI: 10.1002/cyto.a.10011
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone‐induced intracellular oxidative stress in rat hepatoma cells: A flow cytometric assessment

Abstract: Background: Troglitazone (TRO), a thiazolidinedione (TZD) peroxisome proliferator-activated receptor ␥ agonist, was recently withdrawn from the market because of rare but serious hepatotoxicity. Previous studies investigating the cytotoxicity of TRO in cultured rat hepatocytes have conjectured about the role of oxidative stress in TRO-induced hepatotoxicity. Therefore, we investigated whether TRO induces oxidative stress and, if so, the portion of the TRO molecule responsible for the induction of oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 29 publications
6
28
0
Order By: Relevance
“…**p<0.01 and ***p<0.001 vs control. Co Control, Tro troglitazone reports have shown that TZDs affect mitochondrial function and lower ATP production in human hepatocytes and H-2K b muscle cells [11,12,40,41]. Here, we extend these results by demonstrating that troglitazone induces acute mitochondrial membrane depolarisation, activates AMPK and accelerates glucose flux in muscle cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…**p<0.01 and ***p<0.001 vs control. Co Control, Tro troglitazone reports have shown that TZDs affect mitochondrial function and lower ATP production in human hepatocytes and H-2K b muscle cells [11,12,40,41]. Here, we extend these results by demonstrating that troglitazone induces acute mitochondrial membrane depolarisation, activates AMPK and accelerates glucose flux in muscle cells.…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, troglitazone had rare but serious side effects causing subacute irreversible liver injury and failure [9] and was recently removed from the market [10]. In studies geared to uncover the cause of the hepatotoxicity using human or rat hepatocyte cell lines, several mitochondrial abnormalities were observed including the collapse of the mitochondrial membrane potential [11,12]. In those studies, the effect of troglitazone on mitochondrial membrane potential was rapid (within an hour) and occurred at concentrations approximating those considered therapeutically active.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for oxidative stress induced by TZD has been reported by others. 35 The increase in the oxidative stress we found in the liver of ob/ob mice treated with RGZ may be ascribed to a worsening of the mitochondrial function, particularly of the MRC activity. This chain is directly implicated in the generation of ROS and in inducing oxidative stress.…”
Section: Discussionmentioning
confidence: 76%
“…~3-~5 However, according to a MEDLINE search (key terms: rosiglitazone, oxidative stress, antioxidant defense, antioxidant enzymes, NADPH, pentose phosphate pathway, glucose-6-phosphate dehydrogenase, and glutathione; years: no limits), previous studies have demonstrated conflicting results for the effects of rosiglitazone, the second drug in this class to be approved, on oxidative stress and antioxidant defense, and evidence of NADPH-producing metabolic pathways for rosiglitazone is unavailable. 15,16 The aim of this study was to investigate the effects of rosiglitazone treatment, alone or in combination with a high-fat diet, on liver and kidney enzyme activity related to the pentose phosphate pathway and the elimination of reactive oxygen species, and on some metabolic syndrome parameters. We developed a metabolic syndrome model in Wistar rats fed a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%